Hidden Finite, Fused Verbs – the Case for Linguistic Theory in Grammar Instruction - HO THEEN THEEN (The English Teacher, 2016)
The knowledge of the rules governing the structure of a language is undoubtedly a necessity for teachers as a basis for grammar instruction. However, teaching by the book—being able to articulate these ‘grammatical rules’ using standard terminology—does not necessarily mean understanding why the rule is the way it is. This paper posits that linguistic theory can promote a better understanding of how certain rules operate and thus aid teachers in explaining how these rules may be applied. For instance, a prescriptive rule in traditional grammar like “In a yes/no question, if there is an auxiliary verb, the auxiliary verb comes first, followed by the subject, then the main verb” can be explained through the role of the finite in Systemic-Functional Grammar. By manipulating the position of the finite, a proposition (statement) may be argued, i.e. it can be negated or questioned. The paper demonstrates how understanding the underlying linguistic concept can help a teacher to better explain negation and Yes/No questions, including structures involving the auxiliaries ‘do’ and ‘did’, which would otherwise be considered exceptions to the rules that require the learning of even more rules. The paper concludes that knowledge of linguistic theory in addition to knowing grammar rules is essential for effective grammar instruction.